Investigation of diffuse noxious inhibitory controls in the rat monosodium iodoacetate model of osteoarthritis pain - Simmonds, Victoria (2021)
Osteoarthritis (OA) is the most common form of arthritis, with chronic pain being the most frequent and debilitating consequence. Current analgesics are inadequate in treating OA pain due to poor efficacy or serious side effects. Mechanistic studies in humans suggest dysfunction of descending inhibitory pathways in symptomatic knee OA is a key contributor in the development and maintenance of chronic pain. Such inhibitory pathways are recruited by diffuse noxious inhibitory controls (DNIC), whereby inhibition of spinal dorsal horn neuronal excitability to a ‘test’ stimulus can be induced by applying a noxious ‘conditioning’ stimulus to widespread areas of the body outside the peripheral excitatory receptive field (RF) of the neuron (heterotopic stimulation); hence DNIC can be used to study whether inhibition of spinal neural transmission has been compromised. In this respect spinally organised nociceptive withdrawal reflexes (NWRs) are functionally characterised population responses, modularly organised to most effectively move a limb away from a source of pain, with descending inhibitory pathways helping to set an appropriate activation threshold. The aim of this thesis was therefore to investigate whether descending inhibition was altered in an experimental model of OA pain by electrophysiologically measuring DNIC of reflexes in hindlimb muscles.